Bidirectional WDM self-healing ring network for hub/remote nodes - Park, SB; Lee, CH; Kang, SG; Lee, SB (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2003)
We demonstrate a bidirectional wavelength-division-multiplexing self-healing ring network for hub/remote nodes with a single strand of fiber. In this network, self-healing can be achieved within 8 ms. The transmission capacity can be doubled in the operating state. We observed the improvement of power penalty due to the spectral filtering in the realized network with 2.5-Gb/s directly modulated signals.
Keywords: PERFORMANCE